Assessment of Educational Environment of Newly Established Medical College by UG Medical Students: A Mixed Method Study - Srivastava, Ankit; Pathak, Swanand; Singh, Urvashi; Bihari, Anand; Upadhyay, Manisha (Indian Journal of Community Health, 2023)
Introduction: Educational environment always play a crucial role in the development of students as well as faculty of any institution. In India, there is a continuous increase in the number of medical colleges and the number of MBBS seats, but the quality of education with quantity is questionable. To answer this question, the present study was planned to know the educational environment in a new Medical Institution that ejected its alumni in 2018. Aim: To analyze the educational environment of a newly established Medical College in eastern Uttar Pradesh. Materials and Methods: The present study was a descriptive cross-sectional which took six months to complete. This study used the Dundee Ready Education Environment Measure (DREEM) questionnaire, open-ended questions and focus group discussions (FGDs). The study was conducted on MBBS students in Government Medical College, Azamgarh, UP. Results: The batch-wise Global DREEM scores were 169.08 (alumni), 156.23 (interns), 168.76 (2015), 164.16 (2016), 176.23 (2017), 176.94 (2018). This demonstrates that the educational environment is satisfactory in all domains and comes under the 3rd category of the educational environment index. The FGDs showed a positive response in all batches but with high variability in scores, which indicates lack of standardization in Medical Education. The open-ended questions’ responses revealed many merits and demerits about five domains. Conclusion: The variability of DREEM score, FGDs and open ended questions denotes the lack of standardization in the Medical Education system and the scores of the Education Environment Index (all domains) must move from category III (satisfactory) to category IV (excellence).